HUBUNGAN VARIASI METODE PENGAJARAN DAN PENINGKATAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK - Mones, Anselmus Yata (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2020)
The aim of this studi is to measure the relation between the use of variety teaching method and students motivation of study in Catholic Religion Subject. This measurement is done using the qualitative research approach. the level of data validation and its fault is 0,05. The subject of this research is teachers and students at Secondary Schools within Kota Kefamenanu Subdistrict. The statistic data shows that coefficient corelation value is 0,843 or 84,3%. It means that there is a strong and tied relationship between the variable of the use of variety teaching method and students motivation in the proses of learning Catholic Religion Subject. From the percentage value on the relation, the researcher could say that the use of variety teaching method is needed and important for teachers to develop students motivation of studying this certain subject. Students will get more motivated within the process of learning this subject if the teacher applies various teaching methods. Coefficient determination value is 0,710 or 71%. This shows that the use of variety teaching method affects the students motivation of learning 71%, while the rest is 29% affected by any other factors. The other factors here are related to teacher’s personality, giving punishment, and school laws that allow the students to follow learning process at schools. So, there is a significant relationship between the use of variety learning method and students motivation of learning Catholic Religion Subject for Junior High Schools within the Subdistrict of Kota Kefamenanu School Year of 2016/2017. The more the teachers performance in the process of learning the Catholic Religion Subject, the more the students will be motivated to follow the process of learning the subject in the classroom.